2020
DOI: 10.24831/jai.v48i3.33136
|View full text |Cite
|
Sign up to set email alerts
|

Respon Genotipe Talas Colocasia esculenta var esculenta dan var antiquorum pada Interval Pemberian Air Berbeda

Abstract: Talas dikenal sebagai tanaman yang adaptif terhadap tanah dengan kelembaban tinggi. Dalam rangka mitigasi dampak perubahan iklim, respon genotipe tanaman talas terhadap variasi ketersediaan air perlu diketahui. Penelitian bertujuan mengevaluasi pengaruh frekuensi pemberian air pada pertumbuhan dan hasil tanaman talas tipe eddoe dan dasheen. Penelitian dilaksanakan di rumah kaca Kebun Percobaan Cikabayan IPB pada bulan Januari sampai April 2020. Sepuluh genotipe talas dievaluasi yang terdiri atas dua tipe dashe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…In Phaseolus vulgaris, Singh et al ( 2017) revealed that differences in early seedling growth are due to differences in primary nutrients reserved in cotyledons and seed size. The effect of propagule origin, size, and genetic factors are also known to affect early plant establishment in various crops (Kołodziejek, 2017;Singh et al, 2017;Hidayatullah et al, 2020;Maretta et al, 2020;Maghfirah et al, 2022). Kolodziejek (2017) noted that seed coming from the forest has higher viability than those from the roadside.…”
Section: Growth Analysismentioning
confidence: 99%
“…In Phaseolus vulgaris, Singh et al ( 2017) revealed that differences in early seedling growth are due to differences in primary nutrients reserved in cotyledons and seed size. The effect of propagule origin, size, and genetic factors are also known to affect early plant establishment in various crops (Kołodziejek, 2017;Singh et al, 2017;Hidayatullah et al, 2020;Maretta et al, 2020;Maghfirah et al, 2022). Kolodziejek (2017) noted that seed coming from the forest has higher viability than those from the roadside.…”
Section: Growth Analysismentioning
confidence: 99%
“…Anakan adalah anak umbi untuk talas jenis eddoe atau stolon untuk jenis dasheen. Petani biasanya membuang anakan atau stolon untuk jenis dasheen dengan tujuan memaksimalkan produksi, tetapi anakan untuk tipe eddoe biasanya tidak dipisahkan karena anakan yang dihasilkan tipe eddoe tidak memiliki nilai yang dapat dipasarkan (Hidayatullah et al, 2020b)…”
Section: Hasil Dan Pembahasanunclassified
“…In Indonesia, various taro genotypes are popular that grow well in an area such as home garden, farmer field, riverbank, and swampy area [1], but research results showed that taro production was higher in sufficient water conditions. Water treatment at different intervals, 1 and 3days watering resulted in a 2-3 fold increase in tuber fresh weight for all types of taro, compared to taro plants with intervals of watering 7 and 15 days [7], another research reporting that taro plants that were fed 1500 mm per season given once a day, showed the highest results in all components of growth and yield of taro plants [8].…”
Section: Introductionmentioning
confidence: 99%
“…Taro has the potential to fulfill foreign export markets, especially to Japan, this is because in recent years the demand for eddoe type taro from Indonesia has been so high, as much as 100,000 tons of taro per month [9]. One of the obstacles faced by farmers in taro cultivation is low productivity due to the phenomenon of climate change which causes taro to be cultivated in sub-optimal conditions, so studies are needed to obtain adaptive genotypes or keep growing stable and produce high quality tubers under drought and waterlogging condition [7]. The study of plant adaptation to drought and waterlogging can be approached by selecting the right genotype and experimenting with different levels of watering [3], [5].…”
Section: Introductionmentioning
confidence: 99%